The Effect of the Boundary Conditions on the Impact Behaviors of Stitched Composite Lap Joints. Issue 1 (January 2016) - Ergun, Emin; Gökkaya, Ismail
In this study, transverse impact behaviors of stitch adhesively bonded composite lap joints having three different overlap lengths (20, 40 and 60 mm) at different energy levels are investigated. The effects of the boundary conditions (clamped-clamped and clamped-free) and three different span lengths (40, 60 and 80 mm) have been determined. The impacts energies are varied in a range from 5 J to 20 J. Vacuum assisted resin infusion method (VARIM) is used to manufacture composite plates. It is shown that the boundary conditions and span lengths affect considerably the impact responses of the stitch composites lap joints. The important impact characteristics of the composite lap joints are compared with each other and discussed. The observed damages of the composite lap joints are presented.